Corticotropin-releasing factor-related peptides, serotonergic systems, and emotional behavior - Fox, James H.; Lowry, Christopher A. (Frontiers in Neuroscience, 2013)
Corticotropin-releasing factor (CRF) is a 41-amino acid neuropeptide that is involved in stress-related physiology and behavior, including control of the hypothalamic-pituitary-adrenal (HPA) axis. Members of the CRF family of neuropeptides, including urocortin 1 (Ucn 1), Ucn 2, and Ucn 3, bind to the G protein-coupled receptors, CRF type 1 (CRF1) and CRF2 receptors. In addition, CRF binding protein (CRFBP) binds both CRF and Ucn 1 and can modulate their activities. There are multiple mechanisms through which CRF-related peptides may influence emotional behavior, one of which is through altering the activity of brainstem neuromodulatory systems, including serotonergic systems. Corticotropin-releasing factor and CRF-related peptides act within the dorsal raphe nucleus (DR), the major source for serotonin (5-HT) in the brain, to alter the neuronal activity of specific subsets of serotonergic neurons and to influence stress-related behavior. CRF-containing axonal fibers innervate the DR in a topographically organized manner, which may contribute to the ability of CRF to alter the activity of specific subsets of serotonergic neurons. CRF and CRF-related peptides can either increase or decrease serotonergic neuronal firing rates and serotonin release, depending on their concentrations and on the specific CRF receptor subtype(s) involved. This review aims to describe the interactions between CRF-related peptides and serotonergic systems, the consequences for stress-related behavior, and implications for vulnerability to anxiety and affective disorders.